2014
DOI: 10.1128/jvi.01400-14
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MicroRNA miR-526a by Enterovirus Inhibits RIG-I-Dependent Innate Immune Response

Abstract: Retinoic acid-inducible gene I (RIG-I) is an intracellular RNA virus sensor that induces type I interferon-mediated host-protective innate immunity against viral infection. Although cylindromatosis (CYLD) has been shown to negatively regulate innate antiviral response by removing K-63-linked polyubiquitin from RIG-I, the regulation of its expression and the underlying regulatory mechanisms are still incompletely understood. Here we show that RIG-I activity is regulated by inhibition of CYLD expression mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 41 publications
0
65
0
Order By: Relevance
“…However, MLV suppresses the activation of ISG15 and ISG56 induced by IFNs in MARC-145 cells, implying that other mechanisms might contribute to the impairment of IFN-I signaling during PRRSV infection (43). Cellular miRNAs were shown to be used by viruses to evade IFN-I-mediated antiviral responses in host cells (18,21,44,45). However, whether miRNAs participate in PRRSV-mediated evasion of IFN-I-mediated antiviral responses remains elusive.…”
Section: Mir-30c Correlates With Prrsv Infection In Vivomentioning
confidence: 99%
“…However, MLV suppresses the activation of ISG15 and ISG56 induced by IFNs in MARC-145 cells, implying that other mechanisms might contribute to the impairment of IFN-I signaling during PRRSV infection (43). Cellular miRNAs were shown to be used by viruses to evade IFN-I-mediated antiviral responses in host cells (18,21,44,45). However, whether miRNAs participate in PRRSV-mediated evasion of IFN-I-mediated antiviral responses remains elusive.…”
Section: Mir-30c Correlates With Prrsv Infection In Vivomentioning
confidence: 99%
“…To date, 36 Type I IFN-regulated miRNAs have been reported in mammalian systems, targeting genes encoding components of Type I IFN pathway40. Porcine reproductive and respiratory syndrome virus is known to promote infection by upregulating miR-30c, which impairs IFN signaling41, and enterovirus-71 evades the host innate immune response by downregulating the expression of miR-526a, which positively regulates Type I IFN production42. Kaposi’s sarcoma-associated herpesvirus encodes miR-K12-11, which attenuates the IFN response by decreasing I-kappa-B kinase (IKKΔ)-mediated IRF3/IRF7 phosphorylation and inhibiting the activation of IKKΔ-dependent ISGs43.…”
Section: Discussionmentioning
confidence: 99%
“…Its pathogenicity is likely related to its ability to evade host innate immunity [18,19]. Up to date, many studies suggest that the EV71 inhibit host innate antiviral immunity to facilitate its infection [15,25]. Thus, it is important to understand the mechanisms of EV71 infection against the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the elevated level of miR-526a upon virus infections (VSV) led to enhanced RIG-I-mediated IFN-b production by suppressing the expression of CYLD deubiqutinase activity. In contrast, the level of induction of miR-526a by EV71 infection was significantly low with minimal induction of IFN-b [15]. These events promote us to investigate the possibility that removal of polyubiquitination chains from RIG-I upon EV71 infection might contribute to inactivating the RIG-Imediated antiviral response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation